STATE OF THE ART REVIEW: THE EFFECTIVENESS OF IMPLEMENTING PROBLEM BASED LEARNING (PBL) MODELS IN IMPROVING SCIENCE LEARNING - Wulandari, Titis; Tanjung, Yul Ifda; Karlinda; Yohandri; Abdul Razak (Information Technology Education Department, 2026)
The problem based learning model is a student centered learning strategy, which is an innovative that learning model provides active learning conditions . this study aims to measures the effectiveness of research articles on the application of the PBL model to improving science learning. this type of research is a meta- analysis using secondary and quantitative data to draw accurate conclusion in the form of effectiveness by searching the literature from the EBSCO database, Google Scolar and Taylor & Francis. Articles that have been published from 2019-2023. The keywords for cross - sectional studies are as follows: